2005
DOI: 10.1111/j.1527-5299.2005.04458.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Comprehensive Inpatient Education and Discharge Planning Combined With Outpatient Support in Elderly Patients With Congestive Heart Failure

Abstract: Multidisciplinary disease management programs for congestive heart failure have been shown to substantially reduce readmission rates, resulting in a reduction of costs. These interventions, however, have typically included changes in medical management, making it difficult to quantitate the key elements of a successful program involving education, discharge planning, and transitional care in the outpatient setting. The investigators utilized an experienced cardiac nurse educator to coordinate a targeted inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 33 publications
3
100
1
Order By: Relevance
“…54 Similar results were noted in more recent trials evaluating comprehensive discharge planning and immediate outpatient reinforcement in heart-failure patients. Anderson et al report a decrease in 6-month readmissions from 44 to 11% (P = 0.01), 55 whereas Naylor et al reported a decrease in 12-month readmissions from 55 to 45% (P = 0.12), which translated to a significant decrease (P = 0.047) in the total number of readmissions. 56 One trial involving 122 patients discharged from a community hospital assessed the effects of an intervention comprising a comprehensive discharge form electronically transferred to the primary care practitioner (listing discharge diagnosis, dietary and activity instructions, home services, scheduled appointments, pending investigations, discharge medications, postdischarge follow-up and recommendations, nursing comments and patient reminders), telephone contact by a primary care nurse after discharge, and a scheduled clinic review.…”
Section: Studies Of Integrated Pre-and Postdischarge Multicomponent Imentioning
confidence: 91%
“…54 Similar results were noted in more recent trials evaluating comprehensive discharge planning and immediate outpatient reinforcement in heart-failure patients. Anderson et al report a decrease in 6-month readmissions from 44 to 11% (P = 0.01), 55 whereas Naylor et al reported a decrease in 12-month readmissions from 55 to 45% (P = 0.12), which translated to a significant decrease (P = 0.047) in the total number of readmissions. 56 One trial involving 122 patients discharged from a community hospital assessed the effects of an intervention comprising a comprehensive discharge form electronically transferred to the primary care practitioner (listing discharge diagnosis, dietary and activity instructions, home services, scheduled appointments, pending investigations, discharge medications, postdischarge follow-up and recommendations, nursing comments and patient reminders), telephone contact by a primary care nurse after discharge, and a scheduled clinic review.…”
Section: Studies Of Integrated Pre-and Postdischarge Multicomponent Imentioning
confidence: 91%
“…Of 13 studies reviewed in Table 3, 7 studies were RCTs with sample sizes of 192 to 750 participants, 18,20,21,23,27,45,55 rehospitalization was a primary end point in 10 reports, [18][19][20]23,32,45,53,54,56,57 and rehospitalization was measured at multiple time points, from 30 days to 1 year after the index discharge. In 6 quasiexperimental designs, postintervention and preintervention rehospitalization rates were compared, or intervention groups were compared with concurrent control subjects, and sample sizes ranged from 126 to 1393 participants.…”
Section: Rehospitalizationmentioning
confidence: 99%
“…[1][2][3] Multiple exacerbations of CHF result in frequent use of acute health care services by these patients, known as revolving door users. After discharge, 25% of patients are readmitted within the first 30 days, 4,5 and 50% within the first 6 months. 6,7 This frequent use of health care services is mainly due to lack of understanding of a treatment plan, nonadherence to medical therapy, unawareness of CHF symptom exacerbation, and irregular follow-up.…”
mentioning
confidence: 99%